Mars (1564): the initial archaeological investigations of a great 16th‐century Swedish warship. (1st February 2017) - Eriksson, Niklas; Rönnby, Johan
Abstract : Before the Swedish warship Mars exploded and sank in action against a combined Danish and Lübeckian fleet in 1564, it was one of the largest ships in the world. In 2011 the wreck was relocated off the island of Öland in the Baltic Sea. Thanks to the favourable conditions in the brackish water, about two thirds of the hull is preserved on the sea bottom, including the stern with the large sterncastle. The aim of this article is to present initial archaeological observations and results of work since 2011. We briefly describe the historical context and research perspectives regarding this wreck.